Racial Stereotypes, Extended Criminalization, and Support for Breed-Specific Legislation: Experimental and Observational Evidence. (April 2022) - Thompson, Andrew J.; Pickett, Justin T.; Intravia, Jonathan
Scholars have long argued that behaviors and objects associated with criminally stereotyped minority groups can themselves become stereotyped and criminalized, leading to increased punitiveness. Yet, this extended criminalization hypothesis requires theoretical development and direct empirical investigation. To address this issue, we seek to test the concept of extended criminalization, which posits that behaviors associated with racial and ethnic groups accentuate and aggrandize perceived threat of minority groups through a reinforcing process. We examine the extended criminalization hypothesis in the context of breed-specific legislation (BSL). Using data from a survey-based experiment conducted with a sample of young adults from two universities ( N = 525), we test the effects of racial priming on support for laws banning pit bulls. Findings from the experimental manipulation are supplemented with observational findings using measures of racial stereotypes of pit bull owners and breeders. Respondents in the treatment and control groups did not significantly differ in their likelihood of supporting BSL, and the same was true when analyzing Whites separately. The observational findings were consistent with the experimental findings. The findings do not support the extended criminalization hypotheses. Neither racial priming nor stereotypes of pit bull owners and breeders were associated with support for BSL. We outline additional avenues for research on the extended criminalization hypothesis.